The role of the neural reward system in attention selection. Issue 10 (6th July 2016) - Soder, Heather E.; de Dios, Constanza; Potts, Geoffrey F.
Abstract : The prefrontal cortex may play a role in attention selection using motivational information from the mesotelencephalic dopamine system, a neural system that responds to reward prediction violations. If so, neural indices of attention selection and reward prediction violation should have overlapping spatiotemporal distributions. Attention selection elicits a frontal event-related potential component around 200–300 ms, the frontal selection positivity. A component with similar spatiotemporal characteristics, the reward positivity is elicited in reward prediction designs to outcomes that are better than expected. The current study used dense sensor array recording in a sample of 41 participants performing visual oddball (attention) and a reward prediction 'slot machine-like' design to compare the spatiotemporal distributions of the frontal selection positivity and the reward positivity. The components did not differ in their peak latencies and had overlapping scalp topographies, supporting the hypothesis that these positivities represent attachment of incentive salience to perceptual representations in the prefrontal cortex.